Prevalence of depressive symptoms in a memory clinic cohort: a retrospective study - Loreto,F; Fitzgerald,A; Golemme,M; Gunning,S; Win,Z; Patel,N; Carswell,C; Perry,R; Kennedy,A; Edison,P; Malhotra,P (Journal of Alzheimer's Disease, 2022)
Background Depression has been suggested to be a cause of reversible cognitive impairment but also a risk factor for neurodegenerative disease. Studies suggest that depression prevalence may be high in early onset dementia, particularly Alzheimer’s disease, but this has not been systematically assessed in a biomarker-validated clinical dementia cohort to date. Objective To examine the prevalence, features and association with amyloid pathology of lifetime depressive symptoms in a memory clinic cohort meeting appropriate use criteria for amyloid PET imaging.Methods We included 300 patients from a single-centre memory clinic cohort that received diagnostic biomarker evaluation with amyloid PET imaging according to appropriate use criteria. History of lifetime depressive symptoms was retrospectively assessed through structured review of clinical correspondence. Results One-hundred-and-forty-two (47%) patients had a history of significant depressive symptoms (‘D+’). Of these, 89% had ongoing symptoms and 60% were on antidepressants at the time of presentation to our Clinic. Depressive symptoms were equally highly prevalent in the amyloid-positive and the heterogeneous group of amyloid-negative patients.Conclusions Approximately half of patients who meet appropriate use criteria for amyloid PET had a history of depressive symptoms. We suggest that depression is an important feature of both neurodegenerative and non-neurodegenerative cognitive impairment and may contribute to the diagnostic uncertainty behind referral to amyloid PET.